2021
DOI: 10.1016/j.ebiom.2021.103218
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of conditionally reprogrammed cell lines for in vitro chemotherapy response prediction of pancreatic cancer

Abstract: Background: The establishment of patient-derived models for pancreatic ductal adenocarcinoma (PDAC) using conventional methods has been fraught with low success rate, mainly because of the small number of tumour cells and dense fibrotic stroma. Here, we sought to establish patient-derived model of PDAC and perform genetic analysis with responses to anticancer drug by using the conditionally reprogrammed cell (CRC) methodology. Methods: We performed in vitro and in vivo tumourigenicity assays and analysed histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Previous studies have reported an increase in VAF of somatic mutation and an enhanced ability to detect it upon enrichment of cancer cells in patient-derived models. 36,37 Furthermore, it is likely that, given tumor heterogeneity and the small samples size used, the patients enrolled here do not represent full coverage of the ICC spectrum. Thus, future investigations employing larger sample sizes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an increase in VAF of somatic mutation and an enhanced ability to detect it upon enrichment of cancer cells in patient-derived models. 36,37 Furthermore, it is likely that, given tumor heterogeneity and the small samples size used, the patients enrolled here do not represent full coverage of the ICC spectrum. Thus, future investigations employing larger sample sizes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated the efficacy of LDT target sequen-cing panel and CancerSCAN by detecting a sample with high mutation burden and comparing it with the WES results of surgically resected NSCLC (n = 100) samples. The CancerSCAN technique was applied at a clinical level to determine the genomic alterations of target therapy ( 26 - 33 ). In addition, CancerSCAN results showed that a definite number of mutations could be identified and processed as TMB for references.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Lee et al (2019Lee et al ( , 2021 showed that CR technology can be used to establish pancreatic cancer cell lines through biopsies guided by endoscopic ultrasound. CRCs from pancreatic cancer tissues have the same genetic characteristics as those from the primary tumor and can be used for genomic research and drug sensitivity studies and can identify new diagnostic and therapeutic targets for pancreatic cancer (Lee et al, 2019(Lee et al, , 2021. The PDX model has become an important tool for translational research, but there are some limitations, including unsustainable in vitro growth.…”
Section: Application In Digestive Diseases Research Modeling Diseasesmentioning
confidence: 99%
“…However, tissue samples can only be obtained from many advanced cancer patients through fine-needle or core needle biopsy. Research by Lee et al (2019 , 2021) showed that CR technology can be used to establish pancreatic cancer cell lines through biopsies guided by endoscopic ultrasound. CRCs from pancreatic cancer tissues have the same genetic characteristics as those from the primary tumor and can be used for genomic research and drug sensitivity studies and can identify new diagnostic and therapeutic targets for pancreatic cancer ( Lee et al, 2019 , 2021 ).…”
Section: Application In Digestive Diseases Researchmentioning
confidence: 99%